Information System for Services for Making Cover Letters for Family Cards and Resident Identity Cards at the Ngenep Village Office - Fachrudin Pakaja; Maulana Abdul Rahman; HM Amir HM; Muhammad Nasrullah; Rizqiyatul Khoiriyah (International Journal of Information Systems and Technology, 2025)
This study aims to develop an information system for providing cover letters for Family Cards (KK) and Resident Identity Cards (KTP) at the Ngenep Village Office. The system development method uses the SDLC (System Development Life Cycle) approach with stages of planning, analysis, design, development, testing, implementation, and maintenance. The system was built using the PHP programming language and MySQL database. The results show that this system can facilitate the public in submitting cover letter applications online without having to come to the village office, and assist officers in data management and reporting. This system is expected to improve the efficiency of population administration services at the village level.